A VISION OF CHURCH FOR THE FUTURE - Saldanha, Virginia (Asian Horizons, 2015)
The resignation of Pope Benedict XVI brought into public domain the numerous problems the institutional Church is besieged with but the election of a Latin American Pope brought us a ray of hope. A man with his ear to the ground, constantly “reading the signs of the time and interpreting it in the light of the gospel” (Gaudium et Spes, #; hereafter GS), he calls upon the entire Church to transform itself. He outlines the transformation in his first encyclical Evangeli Gaudium [hereafter EG].